Insulinoma and pregnancy: anesthesia and perioperative management - Braga,Angélica de Fátima de Assunção (2017)
Abstract Insulinoma is a functional neuroendocrine tumor derived from beta cells of the pancreatic islets of Langerhans, usually solitary, benign, and curable with surgery (enucleation). It rarely occurs during pregnancy and is clinically manifested by hypoglycemia, particularly in the first trimester of pregnancy. During pregnancy, both conservative therapeutic measures (medication) and surgical treatment are challenging regarding the impossibility of studies on drug teratogenicity as well as the maternal-fetal repercussions during surgery, such as hypoglycemia and changes due to stress. Case report: A 33-year primiparous woman, 86 kg, 1.62 m, BMI 32.7 kg·m-2, at 15 weeks’ gestation, physical status ASA III, investigated for a reduced level of consciousness. Laboratory tests showed: hypoglycemia (45 mg.dL-1) associated with hyperinsulinemia (24 nUI.mL-1), glycosylated hemoglobin (4.1%); other laboratory findings and physical examination were normal. Magnetic resonance imaging showed a 1.1 cm nodule in the pancreatic tail with suspected insulinoma. Due to the difficult glycemic control with bolus and continuous infusion of glucose, laparotomy was performed for tumor enucleation under total intravenous anesthesia combined with epidural block. Monitoring, central and peripheral venous access, radial artery catheterization, diuresis, and glucosimetry were recorded every 15 minutes. Intraoperatively, there was severe hypoglycemia while handling the tumor and shortly before its enucleation, which was controlled through continuous infusion of 10% glucose balanced crystalloid solution (100-230 mL.h-1). The patient's postoperative evolution was uneventful, with resolution of hypoglycemia and total withdrawal of glucose intravenous infusion.